'The refugee' reproduced, negotiated, and represented: hierarchies of Malian refugeeness in Burkina Faso - Bardelli, N (2018)
This dissertation starts from an empirical observation and an intellectual assumption. The former dates from 2013: during a research trip in Burkina Faso I heard and observed humanitarian workers distinguish (in both discourse and practice) between who they thought were 'real refugees' and those who were not, regardless of their legal status. The intellectual assumption is that a category and a label are not only imposed on people designated as such, but are negotiated by the actors themselves and within their interactions with other actors and their social and political economies. Building on these elements, the questions at the centre of this work are: how are hierarchies of refugeeness (re-)produced? And how, when, and why can this (re-) production create or reinforce inequalities among the refugees? I answer these questions by relying on three empirical chapters which focus on different aspects of the construction of refugeeness and the experiences people have and make of 'the refugee' category in the context of Malian forced migration in urban Burkina Faso. More specifically, I look at the encounter of the refugee regime and the refugees' lives through the study of the reproduction, negotiation, and representation of 'the refugee' status and category. What I found and show is how hierarchies of refugeeness can create or reinforce inequalities among the refugees, and how refugeeness, and the possibilities to negotiate with it are unequally produced and distributed, locally but also globally. By unpacking refugeeness through the notion of commodification and relying on ethnographic methods and economic anthropology to study humanitarian interventions, I analyse how the encounter between the refugee regime and the refugees' complex, situated, and varied lives can produce inequalities and is experienced unequally by the refugees themselves.